2016
DOI: 10.1002/chem.201601328
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence of Chiral Perylene Diimide Based Enantiomers Triggered by Supramolecular Self‐Assembly

Abstract: Two perylene diimide (PDI) enantiomers (d/l-PDI) incorporating the d/l-alanine moiety have been designed and synthesized. d/l-PDI in chloroform displays bright-yellow fluorescence that is redshifted to orange-red when the solvent contains a methanol fraction of 99 vol %. No circular dichroism (CD) or circularly polarized luminescence (CPL) signals were observed for d/l-PDI enantiomers in CHCl3 . Interestingly, the d/l-PDI enantiomers exhibit clear mirror-image Cotton effects and CPL emission in the aggregate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…It is noted that at f w = 60%, an induced positive split-type Cotton effect consisting of a positive Cotton effect at 375 nm and a negative Cotton effect at 338 nm was observed in DPCE-ACh aggregates, suggesting the formation of organized helical superstructures in solution. [56][57][58] The maximum absorption anisotropy factor (g CD ) reaches 2.78 Â 10 À3 at 375 nm (Fig. 2C).…”
Section: Chiroptical Properties In Solution and Suspensionmentioning
confidence: 93%
“…It is noted that at f w = 60%, an induced positive split-type Cotton effect consisting of a positive Cotton effect at 375 nm and a negative Cotton effect at 338 nm was observed in DPCE-ACh aggregates, suggesting the formation of organized helical superstructures in solution. [56][57][58] The maximum absorption anisotropy factor (g CD ) reaches 2.78 Â 10 À3 at 375 nm (Fig. 2C).…”
Section: Chiroptical Properties In Solution and Suspensionmentioning
confidence: 93%
“…Additionally, the formation of the ordered chiral nanomaterials resulted in a significant enhancement in the intensity of CPL signals due to the occurrence of chirality transfer from chiral center to perylene moiety. Furthermore, the study was extended using a series of bichromophoric perylenediimide derivatives ( 203 – 205 ) . The results showed that the intensity of CPL signals strongly depended on the self‐assembled states of the molecules, and efficient modulation of bichromophoric systems contributed to the formation of highly ordered aggregation state through intermolecular interactions which is conducive to the enhanced CPL.…”
Section: Supramoleculesmentioning
confidence: 99%
“… 30 , 31 Intelligent control over the CPL handedness is of special significance in smart optoelectronics, information storage, and data encryption. 32 , 33 So far, switching of the CPL handedness is achieved by controlling the system component, such as enantiomers, 34 , 35 solvent, 36 38 coordinating metal ions, 39 solution pH, 40 redox reaction, 41 43 or other alien chemicals. 44 47 Despite the significant progress, inversion of CPL handedness requires changing the composition of the systems, which prohibits their application as smart CPL materials.…”
Section: Introductionmentioning
confidence: 99%